2019
DOI: 10.1002/pssa.201900142
|View full text |Cite
|
Sign up to set email alerts
|

Location and Properties of Carrier Traps in mc‐Si Solar Cells Subjected to Degradation at Elevated Temperatures

Abstract: Multi‐crystalline Si (mc‐Si) solar cells subjected to carrier‐induced efficiency degradation at elevated temperatures are studied using deep‐level transient spectroscopy (DLTS), capacitance‐voltage, and electroluminescence (EL) measurements. Commercially available passivated emitter and rear cell (PERC) mc‐Si solar cells are investigated after short annealing in the dark (at T = 200 °C for 20 min), after degradation by a constant forward current at 70 °C, and after regeneration annealing at 200 °C for 20 min. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…on mesa diodes fabricated from commercial PERC mc-Si solar cells, an almost linear correlation between doping concentration and relative degradation from electroluminescence (EL) imaging was found, as shown in Figure 5. 64 To our knowledge, this is the first time that such a clear correlation between doping and relative degradation has been reported in literature. Despite the fact this correlation is not conclusive on the constituents of the LeTID defect, it suggests dopants are at least interacting to alter the LeTID kinetics and deserves further analysis.…”
Section: Nevertheless From Mchedlidze's Recent Capacitance-voltage Resultsmentioning
confidence: 59%
See 4 more Smart Citations
“…on mesa diodes fabricated from commercial PERC mc-Si solar cells, an almost linear correlation between doping concentration and relative degradation from electroluminescence (EL) imaging was found, as shown in Figure 5. 64 To our knowledge, this is the first time that such a clear correlation between doping and relative degradation has been reported in literature. Despite the fact this correlation is not conclusive on the constituents of the LeTID defect, it suggests dopants are at least interacting to alter the LeTID kinetics and deserves further analysis.…”
Section: Nevertheless From Mchedlidze's Recent Capacitance-voltage Resultsmentioning
confidence: 59%
“…found that degradation rate variations may also arise from lateral doping differences in mc-Si wafers, which increase local currents as suggested by Mchedlidze et al 64 65 (see Figure 4). Even though no conclusive evidence was provided on Niewelt's study, it was argued that the relative changes in PL intensity with degradation (up to 10%) could not be solely accounted by the doping variation in FZ wafers (<5%).…”
Section: Spatial Dependence Of Degradationmentioning
confidence: 68%
See 3 more Smart Citations